Adaptability and stability of soybean genotypes recommended for Alto Paranaíba in Minas Gerais - Matsuo, Eder; Dezordi , Luciel Rauni; Nascimento , Moysés; Cruz , Cosme Damião (Scientia Agraria Paranaensis, 2022)
The cultivation of soybean (Glycine max (L.) Merr.) stands out in the national and world scenario. Brazil, from different points of view, has a high productive capacity of this oilseed, which resulted in the classification of the country as the world’s largest producer. The state of Minas Gerais is one of Brazil’s agricultural granaries, and in soybean culture it is the sixth largest producing state. Thus, the objective was to evaluate the interaction genotypes x environments in soybean genotypes grown in Alto Paranaíba, Minas Gerais, and to identify genotypes with general response, those recommended for favorable or unfavorable environments through the different methodologies of adaptability and stability. Five experiments were conducted in the experimental block design, with four repetitions, in the 2020/2021 agricultural season, in which 14 soybean genotypes were analyzed by productivity, in kg ha-1. An individual analysis of variance was performed (for each environment) along with joint analysis of the experiments, average grouping test (for each environment), decomposition of the interaction between genotypes and pairs of environments and the adaptability and stability analyses were performed. It was concluded that the interaction genotypes x environments was significant and between pairs of environments it was predominantly complex, the genotypes M5917IPRO, TMG7063IPRO and BMXFocoIPRO are recommended for general environment, the genotypes TMG2374IPRO and TMG7363RR are recommended for favorable environments, and the genotypes BS2606IPRO, TEC7849IPRO and BRS5980IPRO are recommended for unfavorable environments.